Pendekatan Manajerial dalam Pemanfaatan Internet untuk Mendukung Bahan Ajar Interaktif - Sabara, Edy; Wahrini, Retyana; Mustamin, Mustamin (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This Community Service Program (PkM) is entitled Training on Searching Teaching Materials from the Internet for Teachers. In the era of globalization, teachers should be more productive in developing teaching materials. Teachers must have broad insight in an effort to improve education. Teachers do not only transfer information/learning materials to students. The material taught by teachers must be varied and not only come from textbooks, but there is information as learning material that can be obtained through other sources. One source that can be used as a medium for searching for the latest information is the internet. The internet is not a rare item nowadays. Almost every time we use the internet in every activity to look for various reference materials and the information we need. Currently in Pangkep district, teachers certainly have a variety of learning media and teaching materials that are used in the teaching and learning process. Teachers can access very diverse information for their teaching materials. After carrying out the Training activity on Searching Teaching Materials from the Internet for Teachers in Pangkep Regency, it can be concluded as follows: The participants were very enthusiastic in taking part in this activity. After the implementing team carried out observations and evaluations, it was discovered that more than 80% of the participants had been able to prepare teaching materials.